Cost-effectiveness of cardiac telerehabilitation in coronary artery disease and heart failure patients: systematic review of randomized controlled trials. Issue 1 (23rd November 2020) - Scherrenberg, Martijn; Falter, Maarten; Dendale, Paul
Abstract: This systematic review aims to assess the cost-effectiveness of cardiac telerehabilitation in comparison with centre-based cardiac rehabilitation (CR). Evidence of cost-effectiveness is an important step towards implementation and reimbursement of telerehabilitation services. Electronic databases were searched for economic evaluations of telerehabilitation programmes. Only randomized controlled trials (RCTs) published in English were eligible for inclusion. Study quality and risk of bias were assessed using the Consensus Health Economic Criteria (CHEC) list. A total of eight economic evaluations met the review inclusion criteria. The total sample size consisted of 751 patients ranging from a minimum of 46 patients to a maximum of 162 patients per study. Maximal follow-up was 5 years. A total of seven of the eight included studies demonstrated that telerehabilitation could lead to similar or lower long-term costs and are thus as cost-effective as traditional centre-based CR. There is significant heterogeneity between all included telerehabilitation interventions in duration, used technology, cost included and follow-up. Based on these small short duration trials, telerehabilitation may be as cost-effective as traditional centre-based approaches. However, more assessments of the value for money of telerehabilitation in larger and longer RCTs are needed both in high- as low-income countries.